Lung Diseases in Inflammatory Myopathies - Barba, Thomas; Mainbourg, Sabine; Nasser, Mouhamad; Lega, Jean-Christophe; Cottin, Vincent (Seminars in Respiratory and Critical Care Medicine, 2019)
Lung involvement is the leading cause of mortality in inflammatory myopathy. A careful assessment of clinical and serologic manifestations especially myositis-associated autoantibodies allows precise classification of the different phenotypes of inflammatory myopathy and stratification of the risk of lung involvement. About three out of four patients with inflammatory myopathy develop interstitial lung disease (ILD), which represents the main cause of morbidity and mortality. In patients with a confirmed diagnosis of inflammatory myopathy, the approach to the diagnosis of ILD includes assessment of clinical and functional severity, evaluation of the high-resolution computed tomography pattern of disease, which often suggests nonspecific interstitial pneumonia or organizing pneumonia. Bronchoalveolar lavage to rule out infection is often performed; however, video-assisted thoracoscopic lung biopsy is now generally discouraged, unless malignancy is suspected. The so-called antisynthetase syndrome characterized by the combination of mechanics' hands, Raynaud' phenomenon, myositis often mild or absent, and presence of one of the anti-tRNA synthetase antibodies is associated with a 70% risk of ILD, especially in subjects with antibodies other than anti-Jo1 antibodies (i.e., anti-PL7 or -PL12 antibodies). Treatment depends on both severity and progression of ILD, often including a combination of corticosteroids and immunosuppressive therapy. Rituximab-based regimen has showed promising results in retrospective studies for the management of refractory or rapidly progressive forms of ILD. Clinical trials are ongoing to evaluate the actual efficacy of this strategy on mortality related to lung disease. Secondary pulmonary complications of inflammatory myopathy include opportunistic infections, aspiration pneumonia, pneumomediastinum, ventilatory failure due to diaphragmatic muscular weakness, drug-induced pneumonitis, and rarely pulmonary hypertension.
Keywords: inflammatory myopathy; dermatomyositis; polymyositis; antisynthetase syndrome; interstitial lung disease; anti-PL7 or -PL12 antibodies